SPECTROSCOPIC STUDIES OF SULFIDES - Wincott P.L.; Vaughan D.J. (My University, 2006)
Spectroscopic methods are the most direct and powerful means of obtaining experimental information on the electronic structures of materials. They also provide crucial information on aspects of crystal structure, crystal chemistry, solution chemistry and chemical speciation in mineralogical or geochemical systems. Many advanced methods for the elemental analysis of solids, surfaces and solutions are also based on various spectroscopies. In this chapter, we review applications of spectroscopic techniques to sulfides, particularly to the bulk solids, but also noting the importance of spectroscopic studies to the investigation of surfaces, fine particle solids, and solutions. Certain of these latter topics, particularly the study of mineral surfaces, are discussed in greater detail in the chapters that follow and will be discussed here only briefly. Not all of the spectroscopic methods employed by mineralogists and geochemists have proved useful in studying sulfides, and the following account focuses on those which have provided the greatest insights. Where we have considered it appropriate, some background information on the principles of a spectroscopic method are provided, as well as references to more comprehensive accounts. We begin with a discussion of the spectroscopies involving the interaction of radiation in the near-infrared–visible–near-ultraviolet region of the electromagnetic spectrum with sulfide minerals, and specifically by discussing optical (electronic) absorption and reflectance spectra. This is followed by an outline of infrared and Raman (vibrational) spectroscopies and their ...